Opportunity as a Threat to Academic Integrity - Anna Armeini Rangkuti (JOURNAL OF EDUCATION, 2011)
This study is aimed at determining the factors most responsible for academic dishonesty in the education students as prospective teachers. Using the quantitative research method, 518 students participated as respondents. Findings show that chances/opportunities have direct and significant impacts on academic dishonesty. Opportunity allows students to commit academic dishonesties without being detected. Opportunities may also be due to ignorance of educational institutions and faculty members to the phenomena of academic dishonesty that occur. Actually, the educational institutions and teaching staff have primary authority in creating academic integrity on campus. Therefore, it is important to create some policies that aim to reduce and even eliminate the opportunities of students to commit academic dishonesties. These policies include: types of exam questions or assignments, clear rules concerning the implementation of evaluation of learning outcomes, as well as a firm associations with academic dishonesty, especially on the part of teachers as those who interact directly with students.